Aspekty genetyczne zwyrodnienia plamki związanego z wiekiem - Janik-Papis, Katarzyna; Zaraś, Małgorzata; Skłodowska, Anna; Ulińska, Magdalena; Borucka, Anna; Błasiak, Janusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Age-related macular degeneration (AMD) is a progressive disease characterized in macula photoreceptors degeneration that leads to loss of central vision in elderly people, especially in developed countries. Many environmental and genetic factors have influence on the occurrence and progression of AMD as well as its form: either dry or exudative. Despite of the extensive research, etiology and molecular background of AMD are poorly understood. Due to advanced biochemical and biophysical techniques some clinical aspects of AMD have been described in details, however, the genetic basis of AMD is still under investigation. The results of some research indicate that the genes, which products may play a role in the pathogenesis of AMD could be CFB, C2, CFHR1, CFHR3, C3, ABCR, APOE, CCL2, CFH, CX3CR1, ERCC6, FSCN2, HMCN1, HTRA1, LOC387715, PLEKHA1, TIMP3 and VEGF-A. The variability of these genes, expressed by their polymorphisms, may also contribute to thye occurrence and progression of AMD. Studying of genetic aspects of AMD many bring results playing a role in the prevention, diagnostics and treatment of this disease.